2015
DOI: 10.1299/mej.14-00410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic vibration on stress relaxation in micro-compression test with step motion

Abstract: In this study, to promote stress relaxation effect by the servo actuated step motion that stops the die motion at regular interval, a novel microforming process with combining ultrasonic vibration and the step motion was proposed. To investigate the effect of ultrasonic vibration on stress relaxation by step motion, a micro-compression test was carried out in different scale dimension with the specimen size of 0.5, 1.0 and 2.0mm in diameter and height. Stress relaxation by step motion was repeated for 6 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This can be explained by the scale effect of the stress relaxation. In our former publication, the amount of stress relaxation increases with decreasing the specimen size in micro-compression test using the step motion or the combined motion [8]. Therefore, the effect of the formability enhancement would become more effective because the stress relaxation is promoted with decreasing the thickness from 0.08 to 0.05 mm.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This can be explained by the scale effect of the stress relaxation. In our former publication, the amount of stress relaxation increases with decreasing the specimen size in micro-compression test using the step motion or the combined motion [8]. Therefore, the effect of the formability enhancement would become more effective because the stress relaxation is promoted with decreasing the thickness from 0.08 to 0.05 mm.…”
mentioning
confidence: 95%
“…This is attributed to the effect of stress relaxation, which suppresses plastic strains leading to localized thinning of the material by the homogeneous deformation. Additionally, authors developed a novel motion combined the step motion with ultrasonic vibration to enhance the stress relaxation [8].We have shown that the amount of stress relaxation increases by combining ultrasonic vibration and it becomes more significant with decreasing the specimen size.…”
Section: Introductionmentioning
confidence: 99%
“…From the last decade, the application of ultrasonic assistance has been attracting increasing attention in microforming. (1)(2)(3)(4)(5)(6)(7)(8) The benefits of ultrasonic vibration in microforming mainly include the surface and volume effects. The surface effect can lower the interfacial friction force between vibrated tools and specimens, (9) resulting in a better surface finishing, (10) and has been well studied in the past.…”
Section: Introductionmentioning
confidence: 99%